Developing Guidebook of Sexual Violence Prevention and Control in Universitas Ahmad Dahlan - Sugiharto, Gatot; Bhakti, Caraka Putra; Rodhiyya, Zaenab Amatillah; Firdaus, Muhammad Yusron (Universitas Ahmad Dahlan, 2024)
Higher education should be a safe and comfortable place for students to receive education. However, in reality, many cases of sexual violence occur in the university environment. Many victims of sexual violence do not dare to report the incident to the authorities. Meanwhile, some victims who have reported their cases have not received a resolution to the problems they complained about. Based on the results of a student needs survey, as many as 64.7% of students need a guidebook for preventing and controlling sexual violence. Based on the survey results, the author aims to research and develop a guidebook for preventing and controlling sexual violence. After going through four stages of R&D 4D model, this guidebook contains the background, scope, juridical and empirical studies, and mechanisms for preventing and controlling sexual violence. Based on the results of media expert validation tests, this book obtained an Index Aiken’s V Coefficient of 0.81 which is in the high category. Meanwhile, the results of material expert validation tests show that the Index Aiken’s V Coefficient of this book is 0.83, which is also included in the high category. This guidebook will be used as a reference in realizing efforts to prevent and overcome sexual violence in the higher education environment, especially at Universitas Ahmad Dahlan.